2021
DOI: 10.1111/tmi.13677
|View full text |Cite
|
Sign up to set email alerts
|

Use of TaqMan Array Cards to investigate the aetiological agents of diarrhoea among young infants with severe acute malnutrition

Abstract: Objectives: Studies involving less sensitive conventional microscopy and culture-based approaches have identified distinct differences in diarrhoeal aetiology in childhood malnutrition. Our study involved the use of an advanced molecular biology technique, the TaqMan Array Cards (TAC), to elucidate the diarrhoeal aetiology among young infants with severe acute malnutrition (SAM). Method: A total of 113 faecal samples was collected from SAM infants, aged 2-6 months, upon admission to the Dhaka Hospital of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…A recent study conducted among Bangladeshi children dwelling in an urban slum found that the most frequently found pathogens in the children with EED and healthy children were EAEC, ETEC, and EPEC ( Chen et al., 2020 ). Prior study in Bangladesh also showed that the detection of EAEC was highest in both severely acute malnourished and well-nourished groups followed by EPEC and ETEC in the malnourished group which is in line with our current findings ( Palit et al., 2021 ). Moreover, a systematic review of the ailment in underdeveloped countries depicted that EAEC, ETEC, and EPEC are the primary pathogens and are accountable for 30-40% of all persistent diarrhea among children ( Abba et al., 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study conducted among Bangladeshi children dwelling in an urban slum found that the most frequently found pathogens in the children with EED and healthy children were EAEC, ETEC, and EPEC ( Chen et al., 2020 ). Prior study in Bangladesh also showed that the detection of EAEC was highest in both severely acute malnourished and well-nourished groups followed by EPEC and ETEC in the malnourished group which is in line with our current findings ( Palit et al., 2021 ). Moreover, a systematic review of the ailment in underdeveloped countries depicted that EAEC, ETEC, and EPEC are the primary pathogens and are accountable for 30-40% of all persistent diarrhea among children ( Abba et al., 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…In underdeveloped nations, diarrhoeagenic strains of Escherichia coli (E. coli) are the prevalent cause of childhood diarrhea, with a higher frequency during the first two years of life ( Gomes et al., 2016 ). They are subdivided into several pathotypes on the basis of their virulence genes which include enteroaggregative (EAEC), enterotoxigenic (ETEC), enteropathogenic (EPEC), shiga toxin–producing (STEC), and enteroinvasive (EIEC), among which EAEC, ETEC, and EPEC are mostly prevalent in developing countries ( Gomes et al., 2016 ; Palit et al., 2021 ). Recent studies found the interaction effect of EAEC with other pathogens on gut inflammation and significant development impairments in children, with MPO concentrations being significantly higher with EAEC coinfection ( Fahim et al., 2018 ; Lima et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 In particular, TaqMan array cards provide a very sensitive method for detecting a wide range of enteropathogens. [10][11][12][13] A study conducted earlier by Rogawski et al assessed the site-specific prevalence of the asymptomatic ETEC infection and its association with LAZ in children at 2 years of age; it is unclear whether the analysis was longitudinal. 8 Moreover, the literature also did not investigate the association between all forms of malnutrition (LAZ, WAZ, and WLZ) and the two pathovariants of ETEC (ST-ETEC and LT-ETEC).…”
Section: Introductionmentioning
confidence: 99%
“… 9 In particular, TaqMan array cards provide a very sensitive method for detecting a wide range of enteropathogens. 10 13 A study conducted earlier by Rogawski et al. assessed the site-specific prevalence of the asymptomatic ETEC infection and its association with LAZ in children at 2 years of age; it is unclear whether the analysis was longitudinal.…”
Section: Introductionmentioning
confidence: 99%
“…In underdeveloped nations, diarrhoeagenic strains of Escherichia coli (E. coli) are the prevalent cause of childhood diarrhea, with a higher frequency during the first two years of life (Gomes et al, 2016). They are subdivided into several pathotypes on the basis of their virulence genes which include enteroaggregative (EAEC), enterotoxigenic (ETEC), enteropathogenic (EPEC), shiga toxinproducing (STEC), and enteroinvasive (EIEC), among which EAEC, ETEC, and EPEC are mostly prevalent in developing countries (Gomes et al, 2016;Palit et al, 2021). Recent studies found the interaction effect of EAEC with other pathogens on gut inflammation and significant development impairments in children, with MPO concentrations being significantly higher with EAEC coinfection (Fahim et al, 2018;Lima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%